Growth of NbC thin film using CH4 as a carbon source and reducing agent - Kim, Kwan Woo; Kim, Bum Jun; Lee, Sang Hoon; Nasir, Tuqeer; Lim, Hyung Kyu; Choi, Ik Jun; Jeong, Byung Joo; Lee, Jaeyeong; Yu, Hak Ki; Choi, Jae Young (Coatings, 2018)
Transition metal carbides (TMCs) have high melting points, hardness, and chemical stabilities in acidic media. In this work, a chemical vapor deposition method using CH4 as a carbon source and reducing agent was employed to make an NbC film. NbCl5 carried by Ar gas was used as an Nb precursor. An NbC thin film, deposited on a c-plane sapphire, exhibited a preferential orientation of the (111) plane, which can be explained by domain-matching epitaxy. A nanoindentation test showed that the NbC film with the preferential orientation of the (111) plane was stronger than that with a random orientation. Moreover, the results showed that H2, which is conventionally used as a reducing agent in NbC synthesis, degraded the crystallinity and hardness of the fabricated NbC.
Keywords: C-plane sapphire; Chemical vapor deposition (CVD); NbC film; Preferential orientation; domain matching epitaxy (DME); Reducing agent; Transition metal carbides (TMCs)